AKURASI KODE DIAGNOSIS UTAMA PADA RM 1 DOKUMEN REKAM MEDIS RUANG KARMEL DAN KARAKTERISTIK PETUGAS KODING RAWAT INAP RUMAH SAKIT MARDI RAHAYU KUDUS PERIODE DESEMBER 2009 - Hetty Rahayu; Dyah Ernawati; Lily Kresnowati (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background: Coding is one of the Medical Record services to support quality services in Hospital. Writing code disease was useful for getting information about group of disease and for an input to decision making for hospital management and getting reimbursement equal for provider health care services. Skill of staff in coding could determine accurate disease code. The aim of research is to examine accuracy main code diagnosis and characteristic of coding’s staff in Mardi Rahayu Hospital, Kudus. Base on result survey on May, 2009, found code diagnosis was not accurate amount 10 % from 30 DRM (document of medical record).Method: Kind research is descriptive by using observation method and interview by cross sectional approach. Populations in research are all of code main diagnosis document medical record in Karmel room pe riod treatment December, 2009. The instrument is used check list, ICD-10 volume 1 and 3. Analysis of data used descriptive in narrative and tabulation form.Result: Base on result observation to main code diagnosis on 148 DRM showed 69.59% data was accurate and 30.41% was not accurate. Staff of coding has been work in coding part in one years ago, has education background Diploma III medical record and health information but they all have not ever follow training coding medical record. Training for coding and give advice to doctors by medical committee was recommended.Keywords: coding, accuracy